Konseling Multikultural : Siswa Korban Intoleransi dan Diskriminasi Berbasis Identitas - Novianti Nensi Liling; Febri Anggiran; Irmani Gelong Pasande'; Ronaldo Stefanus (Pragmatik : Jurnal Rumpun Ilmu Bahasa dan Pendidikan, 2025)
This journal article explores the application of multicultural counseling for students who experience identity-based intolerance and discrimination in school settings. Such experiences often affect students’ psychological well-being, self-esteem, and their ability to grow academically and socially. Multicultural counseling is understood as an approach that places cultural, religious, ethnic, gender, and other personal identity backgrounds at the center of the recovery process. This study highlights the role of counselors in building safe and empathetic relationships, understanding students’ identity dynamics, and applying counseling techniques that align with their lived experiences. The article also emphasizes the importance of collaboration among counselors, teachers, and school administrators in creating an inclusive environment. These efforts include developing anti-discrimination policies, strengthening diversity education, and establishing ongoing support mechanisms. Through a holistic approach, multicultural counseling not only helps students recover from the impact of discrimination but also supports the creation of a school culture that is fair and respectful of differences. This article is intended to serve as a reference for educators and school counselors in designing culturally responsive interventions that address the needs of students affected by intolerance.